Management control systems for sustainable development: a bibliographic study - Oanh Thi Tu Le; Anh Thi Hong Le; Thuy Thi Thanh Vu; Thanh Thi Cam Tran; Cong Van Nguyen (Cogent Business & Management, 2024)
The purpose of this study was to provide a comprehensive review of previous studies on management control systems (MCS). The study tries to evaluate the key aspects that research on MCS mentioned from 1970 to 2023. Using qualitative methods and VOSviewer software, the study collected and analysed data from the Gale Academic OneFile and OpenAlex databases. The paper examined 2279 articles, including 248 from Gale Academic OneFile and 2031 from OpenAlex. The publications were collected based on articles with the keywords `management accounting system' and `sustainable development'. After collection, the articles are classified and arranged according to 6 perspectives. The results show that during the research period (1970–2023), articles on the topic `Control Management' appeared the most with 1850 times. Next are articles with `Business' appearing 1658 times and `Computer science' appearing 1570 times. The topic `Management control system' ranked fourth with 1273 appearances. Results also show that general studies on MCS are conducted with the most significant number of articles (37), with the greatest concentration from 2020 to 2023. The decreasing level includes research on administrative control, detailed control, strategic control, control methods and cultural control. Control tools such as planning and performance measurement also received much attention. The study also found the most influential authors in MCS research (by number of citations and articles) and the countries, universities and journals with the most publications on MCS. The current study provides scholars and researchers with insights from previous investigations into essential areas of MCS. Thereby, it provides a new contribution and comprehensive assessment by highlighting what has been done and what remains to be done in research on MCS. Furthermore, our study reveals future research opportunities and agendas in MCS.
Keywords: M40; M41; O16; 650; Literature review; management accountingsystems; sustainabledevelopment; VOSviewersoftware